Therapeutic Applications of Dental Pulp Stem Cells in Veterinary Medicine: A Case Report - Petchdee, Soontaree; Srionrod, Nitipon; Pattanapol, Nakrob; Bootcha, Ratikorn; Srivatanaku, Petcharin (The Bangkok Medical Journal, 2015)
The application of stem cells treatment has been a considerable research focus over the last decade. Several stem cell types have been studied as the potential candidates to restore the structure and function of damaged tissues and organs. The dental pulp stem cells (DPSCs) have shown potential for their use as a novel alternative resource in dentistry and regenerative medicine. DPSCs have mesenchymal stem cell-like (MSC) qualities, including the capacity for self-renewal and multilineage differentiation potential. In this study, we demonstrate the potential applications of DPSCs as a tool to repair damaged tissues and organs. Diseases related to chronic inflammation such as ischemic heart diseases, osteoarthritis, tendonitis, ocular injury and chronic wounds have been investigated through experimental and clinical trial design to clarify the use of DPSCs therapies. Transplantation of DPSCs provided a good choice in terms of tissue regeneration and healing. Our findings suggested that DPSCs might provide a new perspective for translational medicine. However, important points in DPSCs biology, such as homing and immune-regulation require further study of underlying mechanisms to support the application of DPSCs in the future.